THE JEALOUSY IN CAROL ANN DUFFY’S “MEDUSA” - Prihermawan, Widyanto Tulus (LANTERN (Journal on English Language, Culture and Literature), 2014)
Carol Ann Duffy “Medusa” is a poem which emphasizes the human’s emotion, jealousy. The objectives of this thesis are to show the jealousy in the poem through intrinsic elements, also to explain the jealousy and its effect towards human’s psyche. This thesis uses library research as the method of collecting data. To analyze the extrinsic elements of the poem, this thesis uses mythological and psychological approach in order to understand further about the symbolism and concepts of jealousy. The result of this thesis is that jealousy can cause an adverse change to one’s nature and behavior, emerge an extreme hatred, and lead one into her/his self downfall. It can be concluded that jealousy is an emotion which has negative effects towards human’s psyche.